2008
DOI: 10.1017/s0959259808002700
|View full text |Cite
|
Sign up to set email alerts
|

Gait, aging and dementia

Abstract: Cognitive impairment has been recognized as a risk factor for falls and for increasing the severity of injury following a fall, but the mechanisms by which cognitive impairment influences gait and postural control have been unclear. A recent report that galantamine improves gait parameters in older adults may help to untangle this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 92 publications
0
3
0
1
Order By: Relevance
“…Little is known about the underlying pathophysiology of the motor symptoms in early AD. Later, when the degenerative process spreads to the frontal areas of the brain, gait apraxia is a common finding [11]. Contrary to the original view of AD as involving mainly cortical degeneration, systematic pathological studies have found considerable involvement of brainstem nuclei, which by means of their widespread afferent projections can modulate disparate brain regions to generate integrated motor and cognitive responses [12].…”
Section: Possible Shared Pathomechanisms Underlying the Relationship Between Gait And Cognition • Neurodegenerationmentioning
confidence: 99%
“…Little is known about the underlying pathophysiology of the motor symptoms in early AD. Later, when the degenerative process spreads to the frontal areas of the brain, gait apraxia is a common finding [11]. Contrary to the original view of AD as involving mainly cortical degeneration, systematic pathological studies have found considerable involvement of brainstem nuclei, which by means of their widespread afferent projections can modulate disparate brain regions to generate integrated motor and cognitive responses [12].…”
Section: Possible Shared Pathomechanisms Underlying the Relationship Between Gait And Cognition • Neurodegenerationmentioning
confidence: 99%
“…1 In adults aged 65 years or older, even subtle cognitive impairments are associated with unsteadiness (ie, a high degree of temporospatial variability over consecutive strides), increased dual-task costs (DTCs; ie, gait disturbances induced by performing a concurrent cognitive task, which is often obtained by calculating the percent change in the gait performance from single tasks to dual tasks), and increased risk of falls. 2,3 Diminished dual-task gait performance at baseline is also predictive of future cognitive decline. 4,5 Montero-Odasso and colleagues reported that older adults with mild cognitive impairment who had relatively high DTC to gait speed were more likely to develop dementia in the next 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Gait analysis is the discipline that studies the locomotion and ambulation of people using techniques that branch from a brief observation to sophisticated computerized measurements [5]. Gait analysis is important because human gait may reflect early warning signs of senile dementia and Alzheimer's disease [6] or the assessment of frailty [7]. In addition to this, the recognition of the human gait can be useful to identify the characteristics of the places where people move, which is important for monitoring their activities [8], abnormal behaviors [9], and risk factors [10].…”
Section: Introductionmentioning
confidence: 99%